2017
DOI: 10.1371/journal.pone.0183485
|View full text |Cite
|
Sign up to set email alerts
|

Is routine ophthalmoscopy really necessary in candidemic patients?

Abstract: The purpose of this study was to determine among patients with candidemia the real rate of ophthalmoscopy and the impact of performing ocular assessment on the outcome of the disease. We performed a post hoc analysis of a prospective, multicenter, population-based candidemia surveillance program implemented in Spain during 2010–2011 (CANDIPOP). Ophthalmoscopy was performed in only 168 of the 365 patients with candidemia (46%). Ocular lesions related to candidemia were found in only 13/168 patients (7.7%), of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…In our patients, 46% of survivors and 44% of non‐survivors underwent ophthalmoscopy, and in 4%, endophthalmitis was diagnosed. Our data support the proposition that the benefit of this diagnostic tool is questionable 26 …”
Section: Discussionsupporting
confidence: 87%
“…In our patients, 46% of survivors and 44% of non‐survivors underwent ophthalmoscopy, and in 4%, endophthalmitis was diagnosed. Our data support the proposition that the benefit of this diagnostic tool is questionable 26 …”
Section: Discussionsupporting
confidence: 87%
“…Consecutively, current guidelines recommend an ophthalmological examination of all patients with candidaemia [ 68 , 69 ]. However, more recent studies have reported lower OC rates, from 2.9% to 12.8%, and the necessity for routine ophthalmology consultation has been challenged [ 70 73 ].…”
Section: Screening For Eementioning
confidence: 99%
“…In cases in which no culture was available, the distant infection had to be temporally related with the fungemia and with no alternative cause explaining the clinical condition. Infective endocarditis was diagnosed according to the Duke criteria [17]; ocular candidiasis was classified based on previous criteria [2,5]; septic thrombophlebitis required the presence of venous thrombosis, confirmed by imaging techniques, in the setting of persistent candidemia [10].…”
Section: Definitionsmentioning
confidence: 99%
“…Candida bloodstream infection (BSI) is a lifethreating disease associated with significant morbidity, mortality and high healthcare costs. Complications are frequent [1,2], and mortality ranges between 20 and 45% [3][4][5].…”
Section: Introductionmentioning
confidence: 99%